Hydrogen peroxide‐regulated genes in the Medicago truncatula–Sinorhizobium meliloti symbiosis. Issue 1 (24th January 2013) - Andrio, Emilie; Marino, Daniel; Marmeys, Anthony; de, Marion Dunoyer; Damiani, Isabelle; Genre, Andrea; Huguet, Stéphanie; Frendo, Pierre; Puppo, Alain; Pauly, Nicolas
Summary Reactive oxygen species (ROS), particularly hydrogen peroxide (H2O2), play an important role in signalling in various cellular processes. The involvement of H2O2 in the Medicago truncatula–Sinorhizobium meliloti symbiotic interaction raises questions about its effect on gene expression. A transcriptome analysis was performed on inoculated roots of M. truncatula in which ROS production was inhibited with diphenylene iodonium (DPI). In total, 301 genes potentially regulated by ROS content were identified 2 d after inoculation. These genes included MtSpk1, which encodes a putative protein kinase and is induced by exogenous H2O2 treatment. MtSpk1 gene expression was also induced by nodulation factor treatment. MtSpk1 transcription was observed in infected root hair cells, nodule primordia and the infection zone of mature nodules. Analysis with a fluorescent protein probe specific for H2O2 showed that MtSpk1 expression and H2O2 were similarly distributed in the nodule infection zone. Finally, the establishment of symbiosis was impaired by MtSpk1 downregulation with an artificial micro‐RNA. Several genes regulated by H2O2 during the establishment of rhizobial symbiosis were identified. The involvement of MtSpk1 in the establishment of the symbiosis is proposed.